Improving the quality of learning through lesson plan preparation workshops for an independent learning model - Dita Purwinda Anggrella; Lihar Raudina Izzati; Ahmad Kamal Sudrajat (Universitas Muhammadiyah Malang, 2023)
Making lesson plans is still difficult for some teachers. The lesson plan has too many components, so it takes a long time to design one learning activity. Lesson plan one sheet is the solution to this problem. However, there are still teachers who do not understand how to make a one-sheet lesson plan that suits the needs of students. The purpose of this service activity is to increase the teacher's understanding of the one-sheet lesson plan, so that the teacher can increase the effectiveness of his learning. Therefore, a workshop on making lesson plans was held for Islamic Elementary School teachers in Baki District, Sukoharjo, at Islamic Elementary School 4 Sukoharjo. Previously, a needs analysis was carried out for Islamic Elementary School teachers in Baki District, Sukoharjo. The survey results show that teachers have not consistently made lesson plans. Teachers also have not adapted them to student needs and are only used as administrative requirements in the learning process, so that lesson plans do not have much impact on helping teachers. However, the teacher knows that making lesson plans is the teacher's obligation and feels not burdened. After attending the workshop, the teacher began understanding the independent learning curriculum and designing a one-sheet lesson plan based on student needs. Islamic Elementary School teachers in Baki District, Sukoharjo, feel that a one-sheet lesson plan is more efficient than a regular lesson plan. Through the one-sheet Lesson plan, it is hoped that teachers will be more effective in preparing student learning activities and focus more on the learning process and evaluation to improve the quality of their learning.